The Effectiveness of Islamic Education Programs in Reducing Interest in Online Gambling Among Teenagers - Gunawan, Syahrul; Mutaqin , Jaenal; Zidni, Moh Naufal; Zen, Puad; Suratman; Ibnu Nurrahman, Pandu (Yayasan Mentari Madani, 2024)
This study assesses the role of Islamic education in overcoming online gambling among teenagers. This study evaluates the impact of Islamic education programs on adolescents' interest in online gambling through interviews, observations, and documentation. The findings show that Islamic education is effective in reducing students' interest in online gambling. Values such as responsibility and integrity taught in this program play a role in changing the attitudes and behaviors of adolescents. Interviews revealed that students who took part in the program had a better understanding of the dangers of online gambling and better self-control abilities. Observations showed a decrease in interest in online gambling, an increase in academic achievement, and better social relationships. Documentation from educational institutions confirms the decline in online gambling cases after the program is implemented. Parent support and school supervision strengthen the effectiveness of the program. The active participation of parents and the involvement of the school in implementing Islamic values creates a supportive environment. Islamic education also helps students manage stress and build social solidarity. The results of the study confirm that Islamic education is an effective tool in preventing online gambling among adolescents, with ongoing support from families, schools, and communities